EGFR Monoclonal Antibodies in the Treatment of Squamous Cell Carcinoma of the Head and Neck: A View beyond Cetuximab. (27th September 2012) - Kono, Scott A.; Haigentz, Missak; Yom, Sue S.; Saba, Nabil
Abstract : Squamous cell carcinoma of the head and neck (SCCHN) is a prevalent disease both in the United States and worldwide with an overall poor prognosis, in part due to limited activity of existing therapy. Primary therapy is largely dictated by the anatomical origin of the cancer and whether distant disease is present. Many patients with localized disease are treated with chemoradiotherapy, either in the definitive or adjuvant setting, and those with metastatic disease are treated with palliative chemotherapy. The chemotherapy used in SCCHN can be toxic, whether given with radiation or alone. The epidermal growth factor receptor (EGFR) is highly expressed in SCCHN and serves as a logical therapeutic target. EGFR-directed monoclonal antibodies (MoAbs) have higher activity in SCCHN than small molecule tyrosine kinase inhibitors. Cetuximab, a widely studied EGFR MoAb, is FDA approved in the metastatic setting, as well as with radiation for locally advanced disease. Despite improvements in survival when cetuximab is incorporated with chemotherapy for metastatic disease, the prognosis of patients remains poor. Novel EGFR MoAbs are being developed with the goal of improving efficacy and tolerability. This paper will summarize the use of EGFR-directed MoAbs in treating SCCHN with a focus on novel agents being tested.